2015
DOI: 10.4137/ppri.s12291
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Prevention and Treatment in School-aged Children, Adolescents, and Young Adults—Where Do We Go from Here?

Abstract: The rise in the rate of obesity in school-aged children, adolescents, and young adults in the last 30 years is a clear healthcare crisis that needs to be addressed. Despite recent national reports in the United States highlighting positive downward trends in the rate of obesity in younger children, we are still faced with approximately 12.7 million children struggling with obesity. Given the immediate and long-term health consequences of obesity, much time and effort has been expended to address this epidemic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…41 The subgroup of adolescents in the healthy weight range were significantly more likely than other students to experience weight stability, suggesting that "prevention may be better than cure." 17,42 Prevention trials-focused on preventing healthy-weight children from becoming overweight-have documented moderate-to-strong support for school-based interventions that focus on the kinds of nutrition and physical activity initiatives implemented. Reviews indicate that childhood obesity prevention interventions can be effective in reducing adiposity, especially in the most methodologically rigorous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 The subgroup of adolescents in the healthy weight range were significantly more likely than other students to experience weight stability, suggesting that "prevention may be better than cure." 17,42 Prevention trials-focused on preventing healthy-weight children from becoming overweight-have documented moderate-to-strong support for school-based interventions that focus on the kinds of nutrition and physical activity initiatives implemented. Reviews indicate that childhood obesity prevention interventions can be effective in reducing adiposity, especially in the most methodologically rigorous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study seeks to determine whether these policy interventions are more or less effective for girls or boys and for differences on baseline BMI (i.e., prevention/treatment) based on prior research that has demonstrated these subgroup effects. 16,17…”
Section: Introductionmentioning
confidence: 99%
“…There is plenty of research in the area of childhood obesity and perhaps this very fact testifies that no solution is apparent. Many interventions, be it prevention or treatment of childhood obesity, have shown positive advances but often the followup study indicates that these advances were not sustained over time [7,8,9]. Several of the hundreds of studies surrounding the prevention of or intervention for childhood obesity use motivational interviewing and when placed in a systematic review process the outcome is often positive [12].…”
Section: Methodsmentioning
confidence: 99%
“…The reality of elementary schools: a call for urgent community nutrition programs Objective: In the last decades, the prevalence of overweight and obesity in childhood has been increasing worldwide at an alarming rate [1]. The negative impact of this pandemic is reflected on children's health and is perpetuated in their adulthood [2].…”
mentioning
confidence: 99%
“…The negative impact of this pandemic is reflected on children's health and is perpetuated in their adulthood [2]. It is recognized that preventive strategies are priority in fighting childhood obesity, and that schools are a preferential environment for this approach [1][2][3]. Our aim was to evaluate a cohort of elementary school students to understand the need for preventive community nutrition programs.…”
mentioning
confidence: 99%